Dilacerated distolingual root of mandibular first molar mimicking cementoblastoma: case report by radiographic findings - Dwi Putri Wulansari; Ika Rachmawati; Azhari Azhari (Jurnal Radiologi Dentomaksilofasial Indonesia (JRDI), 2022)
Objectives: This case report aimed to report an extra root number of mandibular first molars that are mimicking benign cementoblastoma in the periapical radiograph and clarified using cone beam computed tomography (CBCT) examination. Case Report: A 22-year-old female patient was referred from private clinic to Radiology Department of Universitas Padjadjaran Dental Hospital for a CBCT examination of the left mandibular first molar with benign cementoblastoma as the provisional diagnosis. Conclusion: It is necessary to consider CBCT examination in order to obtain accurate diagnosis of the presence of distolingual root.